2021
DOI: 10.1152/ajpcell.00403.2020
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA Kcnq1ot1 promotes sC5b-9-induced podocyte pyroptosis by inhibiting miR-486a-3p and upregulating NLRP3

Abstract: Podocytes are epithelial cells adhering glomerular capillaries, which regulate the integrity of glomerular filtration barrier. Irreversible podocyte injury induces glomerular inflammation and causes chronic renal diseases. Kcnq1ot1, a long non-coding RNA (lncRNA), participates in the pathogenesis of diabetic retinopathy and cardiomyopathy. However, its function in podocyte injury is elusive. Pyroptosis of murine podocyte MPC5 was triggered by sublytic complement C5b-9 (sC5b-9) for subsequent in vitro functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…As highly specialized and terminal differentiated cells, podocyte have very limited ability of division and proliferation (Nagata, 2016). When injured by stimulating factors including C5b-9, podocytes are prone to death and eventually abscission occurs (Zhang et al, 2021). In the condition of podocyte death, apoptosis is an important form, and following the production of proteinuria and the progress of IMN.…”
Section: Discussionmentioning
confidence: 99%
“…As highly specialized and terminal differentiated cells, podocyte have very limited ability of division and proliferation (Nagata, 2016). When injured by stimulating factors including C5b-9, podocytes are prone to death and eventually abscission occurs (Zhang et al, 2021). In the condition of podocyte death, apoptosis is an important form, and following the production of proteinuria and the progress of IMN.…”
Section: Discussionmentioning
confidence: 99%
“… Kcnq1ot1 miR-214-3p miR-486a-3p LncRNA Kcnq1ot1 induced pyroptosis in diabetic corneal endothelial kerotopathy [ 155 ]. Kcnq1ot1 induced pyroptosis was due to inhibiting miR-486a-3p and upregulating NLRP3 [ 156 ]. Knockdown Kcnq1ot1 inhibited gasdermin D cleavage to regulate pyroptosis [ 65 ].…”
Section: Pyroptosis In Cancer Metastasismentioning
confidence: 99%
“…Several studies have shown that lncRNAs play an important role in the pathogenesis of diabetes and its complications ( Zhang et al, 2020 ; He et al, 2020 ). We demonstrated that MALAT1 was elevated in the tissue samples from diabetic patients with DGP symptoms as well as in a murine model of DGP.…”
Section: Discussionmentioning
confidence: 99%